Occurrence, Virulence and Antimicrobial Resistance-Associated Markers in Campylobacter Species Isolated from Retail Fresh Milk and Water Samples in Two District Municipalities in the Eastern Cape Province, South Africa - Aboi Igwaran; Anthony Ifeanyi Okoh (MDPI AG, 2020)
Campylobacter species are among the major bacteria implicated in human gastrointestinal infections and are majorly found in faeces of domestic animals, sewage discharges and agricultural runoff. These pathogens have been implicated in diseases outbreaks through consumption of contaminated milk and water in some parts of the globe and reports on this is very scanty in the Eastern Cape Province. Hence, this study evaluated the occurrence as well as virulence and antimicrobial-associated makers of Campylobacter species recovered from milk and water samples. A total of 56 water samples and 72 raw milk samples were collected and the samples were processed for enrichment in Bolton broth and incubated for 48 h in 10% CO2 at 42 °C under microaerobic condition. Thereafter, the enriched cultures were further processed and purified. After which, presumptive Campylobacter colonies were isolated and later confirmed by PCR using specific primers for the detection of the genus Campylobacter, target species and virulence associated genes. Antimicrobial resistance profiles of the isolates were determined by disk diffusion method against a panel of 12 antibiotics and relevant genotypic resistance genes were assessed by PCR assay. A total of 438 presumptive Campylobacter isolates were obtained; from which, 162 were identified as belonging to the genus Campylobacter of which 36.92% were obtained from water samples and 37.11% from milk samples. The 162 confirmed isolates were further delineated into four species, of which, 7.41%, 27.16% and 8.64% were identified as C. fetus, C. jejuni and C. coli respectively. Among the virulence genes screened for, the iam (32.88%) was most prevalent, followed by flgR (26.87%) gene and cdtB and cadF (5.71% each) genes. Of the 12 antibiotics tested, the highest phenotypic resistance displayed by Campylobacter isolates was against clindamycin (95.68%), while the lowest was observed against imipenem (21.47%). Other high phenotypic resistance displayed by the isolates were against erythromycin (95.06%), followed by ceftriaxone (93.21%), doxycycline (87.65%), azithromycin and ampicillin (87.04% each), tetracycline (83.33%), chloramphenicol (78.27%), ciprofloxacin (77.78%), levofloxacin (59.88%) and gentamicin (56.17%). Relevant resistance genes were assessed in the isolates that showed high phenotypic resistance, and the highest resistance gene harbored by the isolates was catII (95%) gene while VIM, KPC, Ges, bla-OXA-48-like, tetC, tetD, tetK, IMI and catI genes were not detected. The occurrence of this pathogen and the detection of virulence and antimicrobial resistance-associated genes in Campylobacter isolates recovered from milk/water samples position them a risk to human health.